Editorial: The Image of a Scientist in the Media - Małgorzata Łosiewicz; Anna Ryłko-Kurpiewska (Jesuit University Ignatianum in Krakow, 2017)
The presented collection of texts constitutes an interdisciplinary study referring to the image of scientists, academic teachers and researchers as described by the media. The reflection contained here refers to the perception of the profession in the light of information published in the internet, press or radio broadcasts, which give an account of the changing image of a scientist. It turns out that Polish science in the face of constant changes is becoming more and more competitive, modern and innovative. It is connected with numerous research problems depicting various ways and forms of passing judgement on scientists...